Going soft and SAD with manganese. - Salgado, P; Walsh, M; Laurila, MR; Stuart, D; Grimes, J (2005)
SAD phasing has been revisited recently, with experiments being carried out using previously unconventional sources of anomalous signal, particularly lighter atoms and softer X-rays. A case study is reported using the 75 kDa RNA-dependent RNA polymerase of the bacteriophase phi6, which binds a Mn atom and crystallizes with three molecules in the asymmetric unit. X-ray diffraction data were collected at a wavelength of 1.89 A and although the calculated anomalous signal from the three Mn atoms was only 1.2%, SHELXD and SOLVE were able to locate these atoms. SOLVE/RESOLVE used this information to obtain SAD phases and automatically build a model for the core region of the protein, which possessed the characteristic features of the right-hand polymerase motif. These results demonstrate that with modern synchrotron beamlines and software, manganese phasing is a practical tool for solving the structure of large proteins.